Reconciling Credit Growth with Economic Stability in Iraq: An Analysis from Siyāsah Māliyah Principles - Gulera Tashkulova; Ahmed Abdulsalam Jghef Mjwal; Saman Salman Rahman; Luma Abdel Hussein Alwan; Nadhema Ahmed Jaff; Mysoon Ali; Saad Qasim Abbas; Aqeel Nadea Abdulateef; Mustafa Mahmood Nuaman (Universitas Islam Negeri Raden Intan Lampung, 2025)
The article aims to assess the general reliability of the BIS credit-to-GDP gap as a macroprudential indicator of financial instability in Iraq, a country characterized by a fragile institution, a large size of the informal sector, and sociopolitical factors. While the BIS measure has attracted global attention as a potential indicator of early warning signs, critics in emerging economies have targeted its one-size-fits-all approach. Through a multi-method approach including statistical analysis, robustness checks, and macroeconomic indicators, this study evaluates the performance of alternative tools like the loan-to-deposit ratio, the ratio of non-performing loans, and credit volatility measures. It further proposes an Islamic economics-based framework, prioritizing ethical lending, risk-sharing, and alignment with the real economic sector. The results show that Iraq's financial system needs a comprehensive model that considers political, institutional, and Sharia-compliant factors. Introducing qualitative parameters and Islamic principles into evaluating financial stability provides a more holistic perception of the repercussions of credit expansion. The article recommends integrating participatory finance instruments, adopting regulatory reforms consistent with Islamic jurisprudence, and enhancing financial inclusion initiatives, particularly in microfinance and digital platforms.